DEVELOPMENT OF AN AUTOMATED CAR–BASED STEM LEARNING MEDIA ON MOTION TOPICS TO FOSTER HIGHER-ORDER THINKING SKILLS OF JUNIOR HIGH SCHOOL STUDENTS - Budi Supiawan; Y Yennita; M. Rahmad; Henni Nopriyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a STEM-based learning medium in the form of an automated car for teaching motion and force concepts as an effort to enhance the Higher-Order Thinking Skills (HOTS) of junior high school students. The background of this research is based on the low level of students’ HOTS in physics learning, limited laboratory facilities, and the continued dominance of conventional teaching methods that provide insufficient meaningful learning experiences. The research employed a Research and Development (R&D) method using the 4D development model, which consists of the Define, Design, Develop, and Disseminate stages. The product developed was a STEM-based automated car learning media package, complemented by a user guide to support instructional activities. Validation was conducted by media experts and subject-matter experts to assess the feasibility of the product in terms of content accuracy, design quality, and functional performance. Furthermore, practicality testing was carried out through limited trials involving science teachers and junior high school students. The results indicate that the STEM-based automated car learning media achieved a valid level of feasibility and a very high level of practicality. These findings suggest that the developed media is easy to use, engaging, and well aligned with students’ characteristics. Therefore, the STEM-based automated car learning media is suitable for use as an alternative instructional tool to support students’ understanding of motion and force concepts while fostering higher-order thinking skills.